2017
DOI: 10.1016/j.amjmed.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Simple NULL-PLEASE Clinical Score in Predicting Outcome of Out-of-Hospital Cardiac Arrest

Abstract: The NULL-PLEASE score was predictive for early in-hospital outcome of out-of-hospital cardiac arrest, with a 3.3-fold greater odds for fatal outcome at the score values of ≥5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…In comparison, both the OHCA and Cardiac Arrest Hospital Prognosis scores are difficult to calculate, needing advanced calculator functions, or nomograms, and are neither easy to calculate, nor clinically friendly. Our results support and extend the findings of the initial validation of the NULL-PLEASE score for death in the emergency department in a small cohort, 14 to now predict survival to hospital discharge, in a large independent cohort, with subsequent validation. Because some 55% of OHCAs are attributable to a cardiac cause, 17 the strong performance of the score in this subgroup is highly pertinent.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In comparison, both the OHCA and Cardiac Arrest Hospital Prognosis scores are difficult to calculate, needing advanced calculator functions, or nomograms, and are neither easy to calculate, nor clinically friendly. Our results support and extend the findings of the initial validation of the NULL-PLEASE score for death in the emergency department in a small cohort, 14 to now predict survival to hospital discharge, in a large independent cohort, with subsequent validation. Because some 55% of OHCAs are attributable to a cardiac cause, 17 the strong performance of the score in this subgroup is highly pertinent.…”
Section: Discussionsupporting
confidence: 84%
“…The score has only been validated to predict death in the emergency department, with a C-statistic of 0.658. 14 Its usefulness for predicting survival in the hospital has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparably identified no-and low-flow time as significant prognostic factors in cardiac arrest [3,[28][29][30][31]. However, data on no-and low-flow times are often estimations or unknown and have been shown to be inaccurate [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they cannot be applied to patients without witnesses of cardiac arrest [4,6]. The "nonshockable rhythm, unwitnessed arrest, long no-ow or long low-ow period, blood pH < 7.2, lactate > 7.0 mmol/L, end-stage chronic kidney disease, age ≥ 85 years, still resuscitation, and extracardiac cause" (NULL-PLEASE) clinical score was devised to identify patients unlikely to survive out-of-hospital cardiac arrest using several unfavorable cardiac arrest-or patient-related characteristics [7]. Recently, the postcardiac arrest syndrome for therapeutic hypothermia (CAST) score and revised CAST (rCAST) score were developed to predict the neurologic prognosis in patients after resuscitation following cardiac arrest, prior to inducing therapeutic hypothermia [10,11].…”
Section: Introductionmentioning
confidence: 99%